Developing an antibiogram for empiric antibiotic prescribing for orthopaedic infections in adult patients at a South African tertiary orthopaedic unit - Arakkal, Ashley (Division of General Surgery, 2024)
Background Empirical antibiotic strategies in the treatment of fracture related infections, chronic osteomyelitis, prosthetic joint infection, and septic arthritis should be based on local microbiological antibiograms. Aim To describe the microbiology and review the antibiogram profiles of bacterial isolates from patients undergoing surgical treatment for non-spinal orthopaedic infections, to identify the most appropriate empirical antibiotic strategy. Methods A retrospective review was performed of all cases of non-spinal orthopaedic infections treated surgically from 1 January 2018 to 31 December 2018. The National Health Laboratory Service microbiology database was used to identify all intra-operative microbiological specimens obtained from orthopaedic patients and data was correlated with the orthopaedic surgical database. Cases were divided into fracture related infections, chronic osteomyelitis, prosthetic joint infection, and septic arthritis. Antibiotic susceptibility data was used to predict the efficacy of different empirical antibiotic regimens. Results A total of 107 cases were included in the study; 184 organisms were cultured. Overall, the most common organism cultured was Staphylococcus aureus (25%) followed by Acinetobacter baumannii (9%), Enterococcus faecalis (7%) and Enterobacter cloacae (5%). Across all categories the oral antibiotic combination with the highest effectiveness (81%) would have been a combination of cotrimoxazole, ciprofloxacin and amoxicillin. The most effective intravenous antibiotic combination would have been either piperacillin-tazobactam, amikacin and vancomycin or meropenem and vancomycin; 90% of tested isolates were susceptible to either of these combinations. Conclusion Antibiogram profiles can serve to guide to empirical antibiotic choice in the management of different categories of non-spinal orthopaedic infections.